Cover Care Homes in a Turbulent Era Care Homes in a Turbulent Era Do They Have A Future? - Armstrong, Pat; Braedley, Susan (Edward Elgar Publishing, 2023)
This thoughtful book provides a refreshing, comparative perspective on the future of care homes in our post-pandemic world. Building on more than a decade of collaborative international and interdisciplinary research in Canada, Germany, Norway, Sweden, the UK and the US, it employs a feminist political economy framework to address the key challenges facing care homes in this turbulent era.